What is the evidence on indirect drivers of biodiversity loss worldwide? A systematic map protocol - Federico Grossi; Daniel I. Avila-Ortega; Anne-Sophie Crépin; Elina A. Virtanen; Enrico Di Minin (PLoS ONE, 2026)
An estimated 1 million species of animals and plants are threatened with extinction. While much research has concentrated on direct drivers (e.g., land use change) of biodiversity loss, understanding the indirect (e.g., economic, demographic, and institutional, etc.) drivers triggering these direct drivers is a research priority. Systematic reviews of literature mapping the links between indirect and direct drivers and where, when, how, and what biodiversity they affect are missing. The primary research question of this systematic map will be: What is the evidence on indirect drivers of biodiversity loss worldwide ? Eligible studies must include information on the links between direct and indirect drivers and how they affect biodiversity. Outcomes will be categorized by species, taxonomic groups, ecological levels of organization, geographical scope, and both direct and indirect drivers of biodiversity loss. We will implement a thorough and repeatable three-stage screening process through peer-reviewed articles, and a searchable database will be made publicly accessible as an interactive online resource. This systematic map will help identify knowledge gaps and enhance our understanding of the underlying causes of biodiversity loss.